The social foundations of emotion : developmental, cultural, and clinical dimensions - Hofmann, Stefan G.; Doan, Stacey N. (American Psychological Association, 2018)
In this book, Stefan Hofmann and Stacey Doan argue that emotions cannot be understood without taking into account the rich, dynamic social and cultural worlds we inhabit. Only by understanding the client's social world in all its complexity can clinicians fully treat common mental health problems, such as depression and anxiety.